Quantifying nitrogen leaching in wheat (Triticum aestivum L.) using lysimeter stable isotope conservative tracer and modelling techniques - Van der Laan, Michael (University of Pretoria, 2018)
Dissertation (MSc (Agric))--University of Pretoria, 2017.